RECEPTION ANALYSIS OF @DYANDRAACADEMY INSTAGRAM FOLLOWERS ON #BELAJARBARENGDYANDRA CAMPAIGN AS EVENT MANAGEMENT LEARNING MEDIA - Devinta Cahya Ramadhanti; Emilianshah Banowo (Politeknik Negeri Media Kreatif, 2025)
The increasing interest of the younger generation in the event industry, along with the growth of this sector in Indonesia, has encouraged universities and non-formal institutions to provide more structured learning opportunities. One alternative is the educational campaign #BelajarBarengDyandra conducted on Instagram @dyandraacademy, which introduces knowledge about event management in a practical way. The purpose of this study is to find out how followers perceive the campaign as a learning medium. The research uses Stuart Hall’s reception analysis model, which divides audience interpretation into dominant, negotiated, and oppositional positions. A qualitative descriptive method was employed through in-depth interviews with eight participants aged 18–25 years, supported by triangulated information from campaign organizers. The results show that most informants fall into the negotiated position, while a smaller number are in the dominant position. The conclusion indicates that #BelajarBarengDyandra functions as an initial learning platform about event management, although it cannot fully replace direct or formal learning.